Perceived teachers’ behavior and students’ engagement in physical education: the mediating role of basic psychological needs and self-determined motivation - Leo, F. M.; Mouratidis, A.; Pulido, J. J.; López-Gajardo, M. A.; Sánchez-Oliva, D. (Physical Education and Sport Pedagogy, 2022)
Background: Although several studies that rely on self-determination theory have shown the positive interrelations among perceived need supportive learning environment, needs satisfaction, quality of motivation, and desired outcomes in the context of physical education, only few studies have tested so far the full sequence of relations within a single integrated model. Purpose: The main aim of this study was to test whether indeed needs satisfaction and in turn quality of motivation mediate the relations of need supportive learning environment to physical activity engagement and intentions. Method: Participants were 1120 Spanish students (49.9% males; Mage = 11.70 years; SD = 1.63; range = 10–17 years) from 30 classes out of 13 primary and secondary schools. Results: The multilevel path model showed a positive relation of perceived need-supportive teaching to physical activity engagement and intentions by means of needs satisfaction and autonomous motivation and a negative relation of perceived need-thwarting teaching to engagement and intentions by means of needs frustration and amotivation. Although controlled motivation was found to associate with need frustration and need-thwarting teaching it was not associated with engagement and intentions. Conclusion: the present findings suggest that the type of teaching style employed by the teachers is decisive to achieve positive consequences in physical education students. © 2020 Association for Physical Education.